A DEVELOPMENT OF GRAMMATICAL COMPETENCE IN ENGLISH LANGUAGE IN STUDENTS OF NON-PHILOLOGICAL EDUCATION: DEVELOPMENT OF GRAMMATICAL COMPETENCE IN ENGLISH LANGUAGE IN STUDENTS OF NON-PHILOLOGICAL EDUCATION - Almatova, Umida (Журнал иностранных языков и лингвистики, 2022)
The article considers the growing need of grammatical accuracy in both formal and informal intercourse. As language is the core element of human existence and grammar is the cornerstone of organizing our thoughts correctly, we can achieve full understanding of it only by learning it thoroughly and continually. Moreover, it is proven in this article that mastering the grammar of one language can ease the acquisition of other languages. Hence, nominating grammar as the 5th competence of language acquisition is not accidental and it plays a foremost role in all linguistic dimensions.